2021
DOI: 10.1016/j.actatropica.2020.105778
|View full text |Cite
|
Sign up to set email alerts
|

One year update on the COVID-19 pandemic: Where are we now?

Abstract: Highlights COVID-19 pandemic has sparked a research revolution to understand the disease and find a cure. The past year has seen rapid advances in understanding the biology of SARS-CoV-2 and developing therapeutics. Three vaccines have recently cleared phase III trials (BNT162b2, Sputnik V, and mRNA-1273 vaccine). At the pandemic's 1-year mark, we summarize information on SARS-CoV-2 gathered in the past year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0
15

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 164 publications
1
157
0
15
Order By: Relevance
“…The rapid availability of more SARS-CoV-2 genomes, most of which differ by one or few mutations, enables the accurate investigation into spread patterns. Genomic epidemiology-based analysis is being used to control the rapidly spreading SARS-CoV-2 outbreak ( Mishra and Tripathi, 2021 ). Combined with the availability of more genomic data, our information on mutation repertoires is critical for predicting structural features that may guide the design of new drugs to counter resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid availability of more SARS-CoV-2 genomes, most of which differ by one or few mutations, enables the accurate investigation into spread patterns. Genomic epidemiology-based analysis is being used to control the rapidly spreading SARS-CoV-2 outbreak ( Mishra and Tripathi, 2021 ). Combined with the availability of more genomic data, our information on mutation repertoires is critical for predicting structural features that may guide the design of new drugs to counter resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…A closer inspection of interactions and energy components revealed that the hydrogen bonds and van der Waals pairs contributing to the hydrogen bond and van der Waals energies largely governed the difference in the total stabilizing energy and between the affinity of the RBD/ACE2 complex in its apo-RBD/ACE2 and RBD/ACE2-arbidol complexes ( Table 3 ). ( Mishra and Tripathi, 2021 ) ( Wang et al, 2020e ) ( The, 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the above proteases, the neutrophil elastase is enriched in the nose of humans compared to other tissues ( 19 ) and neutrophils, a source for this elastase, are recruited to the nose in SARS-CoV-2 infection ( 20 ). Indeed, the now worldwide dominant Asp614Gly variant, introduced a new elastase proteolysis site in the spike protein ( 2, 21 ). Using ExPASy ( 22 ), we identified Thr716Ile and Ser982Ala in 501Y.V1 as potential new elastase cleavage sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Identified first in the second week of October, this variant became dominant in South Africa within a month. Six fixed substitutions in all the South African variants were identified (Table 1b): Asn501Tyr [identical to the 501Y.V1 UK variant ( 11 )] and Pro614Gly [identical to the European dominant variant, identified between March and April of 2020 ( 2 )], the Asp80Ala, Lys417Asn, Glu484Lys and Ala701Val. It appears that the combination of these substitutions results in increased infectivity without increasing COVID-19 severity ( 13 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation